2020
DOI: 10.1186/s13567-020-00809-6
|View full text |Cite
|
Sign up to set email alerts
|

EtMIC3 and its receptors BAG1 and ENDOUL are essential for site-specific invasion of Eimeria tenella in chickens

Abstract: Avian coccidian parasites exhibit a high degree of site specificity in different Eimeria species. Although the underlying mechanism is unclear, an increasing body of evidence suggests that site specificity is due to the interaction between microneme proteins (MICs) and their receptors on the surface of target host cells. In this study, the binding ability of E. tenella MICs (EtMICs) to different intestinal tissue was observed by immunofluorescence to identify the key surface molecule on the parasite responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…MIC, we found a similar pattern to the other E. tenella genes, some were strongly downregulated across time points such as two versions of AMA1 , and others appeared to be focused in the merozoites, such as AMA1_iso1 and EtMIC3 . Interestingly, EtMIC3 has been pointed out as important for E. tenella tissue specificity to the caecum (Li et al ., 2020 ). In the case of the AMA1 paralogues, AMA1 and AMA1_iso2 both were expressed across all time points in the present study, though downregulated, while AMA1_iso1 was almost exclusively expressed in the late time points.…”
Section: Discussionmentioning
confidence: 99%
“…MIC, we found a similar pattern to the other E. tenella genes, some were strongly downregulated across time points such as two versions of AMA1 , and others appeared to be focused in the merozoites, such as AMA1_iso1 and EtMIC3 . Interestingly, EtMIC3 has been pointed out as important for E. tenella tissue specificity to the caecum (Li et al ., 2020 ). In the case of the AMA1 paralogues, AMA1 and AMA1_iso2 both were expressed across all time points in the present study, though downregulated, while AMA1_iso1 was almost exclusively expressed in the late time points.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins involved in host-cell invasion have been proposed as promising vaccine candidates ( Vermeulen, 1998 ). Microneme proteins (MICs), for example, function in the adhesion to the host cell during invasion by coccidian parasites and exhibit promising protective efficacy against infection by Eimeria species ( Carruthers and Tomley, 2008 ; Cowper et al, 2012 ; Li et al, 2020 ). Lai et al (2011) reported that MIC3 from Eimeria tenella (EtMIC3) contributed greatly to the cecal tissue tropism of E. tenella in early invasion ( Lai et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that EtMIC3 protein consists of seven microneme adhesive repeats (MARs), including four highly conserved internal repeats and three divergent external repeats [ 7 , 25 ]. EtMIC3 contributes to guiding and binding sporozoites to the invasion site in chicken intestinal tract by recognizing BCL2-associated athanogene 1 (BAG1) and Endonuclease polyU-specific-like (ENDOUL) [ 26 ], and sialylated glycans [ 12 , 13 ]. It was reported that AMA1-binding peptides effectively inhibited T. gondii, P. falciparum and E. tenella invasion into host cells [ 14 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%